1997
DOI: 10.1200/jco.1997.15.5.2030
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant postoperative fluorouracil-modulated chemotherapy combined with pelvic radiation therapy for rectal cancer: initial results of intergroup 0114.

Abstract: There is no evidence at present for a beneficial effect of levamisole in the adjuvant treatment of rectal cancer. Definitive evaluation of the effect of the addition of leucovorin to 5-FU and pelvic radiation will require further follow-up evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(78 citation statements)
references
References 17 publications
3
68
1
6
Order By: Relevance
“…Clinical trials commonly report physiciangraded diarrhea, which may not fully capture the QOL effects from the patient's perspective and may underrepresent the true prevalence of this symptom. Although previous studies have reported an approximately 30% rate of physician-reported, acute, grade 2 to 5 diarrhea, [1][2][3]5 in clinical practice, it is observed more commonly. In addition, other treatment-related, acute GI symptoms are observed frequently in the clinic but are not described well in the literature.…”
Section: Original Articlementioning
confidence: 83%
“…Clinical trials commonly report physiciangraded diarrhea, which may not fully capture the QOL effects from the patient's perspective and may underrepresent the true prevalence of this symptom. Although previous studies have reported an approximately 30% rate of physician-reported, acute, grade 2 to 5 diarrhea, [1][2][3]5 in clinical practice, it is observed more commonly. In addition, other treatment-related, acute GI symptoms are observed frequently in the clinic but are not described well in the literature.…”
Section: Original Articlementioning
confidence: 83%
“…26 One report recommended caution in the interpretation of the subgroup analyses, because the gender analysis was not planned in advance. 28 Those authors also pointed out that their results suggested that dosing schemes may need to be different for men and women and that other studies of adjuvant treatment in patients with colorectal carcinoma should evaluate gender-related differences. 28 The study that reported higher rates of pretreatment distress among women recommended that women may need more psychological support before treatment and early in the course of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…28 Those authors also pointed out that their results suggested that dosing schemes may need to be different for men and women and that other studies of adjuvant treatment in patients with colorectal carcinoma should evaluate gender-related differences. 28 The study that reported higher rates of pretreatment distress among women recommended that women may need more psychological support before treatment and early in the course of treatment. 27 That study was done specifically to evaluate quality-of-life differences between women and men with lung cancer, because increasing numbers of women are affected by lung cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distal rectal cancer operations are still a challenge, even for experienced surgeons, where laparoscopic approach is gaining popularity, and neo-adjuvant therapy is a standard for II-nd and III stage of the disease. 1,2 Laparoscopic, compared to conventional operations have been advocated to have less complications, 3 concerning the most common ones -surgical site infection (SSI), anastomosis leakage, post-operative ileus and bleeding, all assessed by Clavien-Dindo classification. 4 Anastomosis insufficiency rate in colorectal surgery varies from 2 to 26%, 5,6 being higher in low and ultralow rectum resections.…”
Section: Introductionmentioning
confidence: 99%